Use of algae from an oasis in Saudi Arabia in production of biofuel and bio-fertilizer - El Semary, Nermin Adel; Mahdi, Howrah; Alnoaim, Abrar; Alsofan, Kawther Heji; Almsthi, Sarah Ibrahim; Albader, Wed Saleh (Bangladesh Journal of Botany, 2018)
AlAhsa oasis in Saudi Arabia is one of the largest oases in the world. Algae, from this region have been under-explored in the past decades. A study was conducted with Chlorococcum strain to produce biofuel alongside the seaweed Hormophysa cuneiformis. Gas Chromatography/Mass Spectrometry of fatty acid composition showed that the biodiesel obtained had limited number of unsaturated fatty acids as compared to the number of saturated fatty acids present, which indicates the stability of the produced biodiesel. Thereby the use of algal biomass for the production of biofuel is feasible. Moreover, the biomass may serve other different biotechnological applications. To further test this hypothesis, the aqueous extract of two different algae; one derived from the blue green alga (cyanobacterium) Phormidium sp. and the other from brown alga Hormophysa cuneiformis was used as liquid biofertiliser at concentrations of 50 and 10% of both algae. Sterilized Vigna seeds were soaked in the extracts for two days. Seeds were sown in sterilized soil and the germination percentage as well as shoot and root lengths were recorded for developing seedlings. The results showed that there was a significant increase in seed germination rate compared to control. Similarly, there was a significant increment in the length of root and root system compared to control with the 50% aqueous extract concentration being highest in growth parameters for brown alga followed by blue-green alga possibly due to the presence of growth stimulants in these extracts.